Evaluation of antibacterial efficacy of garlic (Allium sativum) and ginger (Zingiber officinale) crude extract against multidrug-resistant (MDR) poultry pathogen (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study is aimed to understand the antibacterial sensitivity of native and Indian varieties of garlic (Allium sativum) and ginger (Zingiber officinale) crude extracts against multidrug-resistant (MDR) poultry pathogen (Escherichia coli and Salmonella sp.). Materials and Methods: Thin layer chromatography (TLC) is used to identify the target spices’ bioactive antibacterial compounds. MDR E. coli and Salmonella sp. were isolated from poultry. The TLC-Bioautography technique was applied to explore the antibacterial potentiality of garlic and ginger. Results: Inhibitory activities of garlic were Zone of inhibition (ZI) = 14.03 ± 0.15 mm and 19.70 ± 0.36 mm, Minimum inhibitory concentration (MIC): 0.625 and 0.325 mg/ml, and ginger were ZI = 14.63 ± 0.30 mm and 11.56 ± 0.51mm, MIC: 9.0 mg/ml against E. coli and Salmonella sp., respectively. Two bands of garlic (Rf value = 0.31 and 0.50) and one band of ginger (Rf value = 0.71) showed inhibitory potential in TLC-Bioautography against both MDR isolates. Conclusion: Garlic and ginger were effective against MDR E. coli and Salmonella sp. These spices could be a suitable alternative during the antibiotic void.J. Adv. Vet. Anim. Res., 10(2): 151–156, June 2023http://doi.org/10.5455/javar.2023.j664